Service quality and internal customer satisfaction amidst the pandemic - Nor Hafizah Ibrahim,; Zafir Khan Mohamed Makhbul,; Che Wan Kamarul Hishysam Che Wan Ahmad,; Syarifah Nurfuaduz Zakiah Habib Dzulkarnain, (Penerbit Universiti Kebangsaan Malaysia, 2024)
The onset of the COVID-19 pandemic has brought about substantial changes in service quality within Higher Education Institutions, particularly impacting Human Resource Management (HRM). Consequently, there is an urgent need to enact measures that enhance service quality, given the pivotal role of HRM services in shaping organisational performance. To achieve this, it is imperative to consistently monitor and augment HRM service quality in alignment with organisational objectives. This study sets out to gauge the levels of satisfaction among HRM customers concerning the quality of HRM services at a specific public university in Malaysia. To achieve this objective, a meticulously crafted questionnaire was developed, taking into account the fundamental determinants of service quality and the dimensions outlined in the SERVQUAL model. A pilot study was undertaken to ascertain the questionnaire’s reliability, revealing a commendably high Cronbach’s Alpha Coefficient of 0.957. Subsequently, an online survey was conducted, reaching out to the entire population of 17,000 respondents. Employing purposive sampling, the study gathered 802 completed questionnaires. The research methodology hinged on correlation and regression analyses to scrutinise the intricate relationship between service quality dimensions and customer satisfaction. The findings underscored the significant influence of all dimensions - Responsiveness, Assurance, Access, Empathy, and Reliability - on customer satisfaction, with the exception of Tangible. This study provides invaluable insights for managerial decision-making, presenting a strategic roadmap to pinpoint areas for enhancement and to develop forward-looking strategies that adapt to the ever changing landscape of HRM service quality amid uncertain conditions such as the COVID-19 pandemic.